Metode Naive Bayes Mendeteksi Penyakit Citrus Vein Phloem Degeneration - Santoso, Apira Nurul Putri; Santi, Rina Candra Noor (STIKOM Tunas Bangsa Pematangsiantar, 2023)
On domestic and international markets, oranges are the largest commodity in the category of fruit imports and exports. In Indonesia alone, almost all regions of Indonesia grow citrus fruits, but these plants can be affected by a variety of other diseases, one of which is Citrus Vein Phloem Degeneration in citrus leaf veins. The disease is characterized by symptoms of yellow spots around the leaves, but Indonesia itself does not have a system that can detect the severity of the disease and farmers must be able to detect it manually based on experience. This system is expected to help farmers identify the severity of the disease from leaf images. The processing steps used include trimming, resizing, preprocessing with RGB to grayscale conversion, edge detection with Sobel, feature extraction with GLCM, and naive Bayes classification. In addition, the accuracy obtained from the test results is 67.58%.